2009
DOI: 10.1007/978-0-387-76483-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of boundary layer flow over a moving thin needle with variable heat flux

Abstract: Abstract:The problem of steady laminar forced convection boundary layer flow of an incompressible viscous fluid over a moving thin needle with variable heat flux is considered. The governing boundary layer equations are first transformed into non-dimensional forms. These equations are then transformed into similarity equations using the similarity variables, which are solved numerically using an implicit finite-difference scheme known as the Keller-box method. The solutions are obtained for a blunt-nosed needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In order to integrate the corresponding I.V.P., the values of F �� ( = 0) , � ( = 0) and � ( = 0) are required. However, such values do not exist after the non-dimenzionalization of the boundary conditions (6)- (7). Suitable guess values for F �� ( = 0) , � ( = 0) and � ( = 0) are chosen and then numerical integration was carried out.…”
Section: Classical Runge-kutta Methods Along With Shooting Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to integrate the corresponding I.V.P., the values of F �� ( = 0) , � ( = 0) and � ( = 0) are required. However, such values do not exist after the non-dimenzionalization of the boundary conditions (6)- (7). Suitable guess values for F �� ( = 0) , � ( = 0) and � ( = 0) are chosen and then numerical integration was carried out.…”
Section: Classical Runge-kutta Methods Along With Shooting Techniquesmentioning
confidence: 99%
“…incompressible flow on a paraboloid of revolution. Ahmad et al [7] reported the boundary layer flow over a moving thin needle with variable heat flux during 12th edition of WSEAS International Conference on Applied Mathematics. In another related research by Ishak et al [8], boundary layer flow on a moving isothermal object with variable thickness parallel to a moving stream was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Cebeci and Na [2] investigated the laminar free convection heat transfer from a needle. Ahmad et al [3] examined the boundary layer flow over a moving thin needle with variable heat flux. The boundary layer flow over a stretching surface with variable thickness was analyzed by Fang et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cebeci and Na [3] investigated the laminar free convection heat transfer from a needle. Ahmad et al [4] examined the boundary layer flow over a moving thin needle with variable heat flux where they observed that the wall temperature was significantly influenced by both the needle size parameter and the Prandtl number. Boundary layer flow over a stretching sheet with variable thickness was studied by Fang et al [5].…”
Section: Introductionmentioning
confidence: 99%